A note on money creation in emerging market economies - Alexey Ponomarenko (Bank of Finland, Institute for Economies in Transition (BOFIT), 2016)
This paper discusses the money creation mechanisms in emerging markets with special focus on external transactions. We argue that one should not rule out the possibility that fluctuations in the loans-to-deposits and non-core liabilities ratios are driven by the banks. We also argue that, under a flexible exchange rate regime in which the central bank is not trying to accumulate foreign reserves, external transactions are unlikely to contribute significantly to money growth. To make our argument, we analyze a historical episode of these flows in Korea and Russia and conduct a canonical correlation analysis for a cross-section of emerging market economies.
URN:NBN:fi:bof-201603171039
Keywords: E51; F30; G21; 330